Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T19:44:10+01:00
A) -(2a-3b+5)+(4a-7b+3)-(3a-2b-1)= -2a+3b-5+4a-7b+3-3a+2b+1 = -a-2b-1

b) (4a+2b-7)-(a-3b-4)-(2a-b-3)= 4a+2b-7-a+3b+4-2a+b+3 = a+6b

c) -(-2a-5b-4)+(2a-3b-4)-(-3a-b+2)= 2a+5b+4+2a-3b-4+3a+b-2 = 7a+3b-2

d) (-5a+b-3)-(2a-3b+5)-(4a-b-8)= -5a+b-3-2a+3b-5-4a+b+8 = -11a+5b
11 4 11
2010-02-04T19:45:22+01:00
A) -(2a-3b+5)+(4a-7b+3)-(3a-2b-1)=
-2a+3b-5+4a-7b+3-3a+2b+1=-a-2b-1
b) (4a+2b-7)-(a-3b-4)-(2a-b-3)=
4a+2b-7-a+3b+4-2a+b+3=a+6b
c) -(-2a-5b-4)+(2a-3b-4)-(-3a-b+2)=
2a+5b+4+2a-3b-4+3a+b-2=7a+3b-2
d) (-5a+b-3)-(2a-3b+5)-(4a-b-8)=
-5a+b-3-2a+3b-5-4a+b+8=-11a+5b
4 4 4